KAZAKHSTAN AND AZERBAIJAN IN 1991: RESTORATION OF INDEPENDENCE OR FORMATION OF NEW STATES? (Journal of actual problems of jurisprudence, 2026)
The article is devoted to the analysis of the restoration and emergence of the statehood of Kazakhstan and Azerbaijan in 1991 in the context of international and national law. It is noted that both republics affirmed their statehood in the international community: Kazakhstan as a new independent state forming its international legal status “from a zero point,” and Azerbaijan relying on the concept of succession to the Azerbaijan Democratic Republic (ADR) and the restoration of its international legal identity. The article analyzes international concepts of continuous legal personality, procedures for the recognition of states, and the practice of international recognition of new and restored subjects of international law.It is also noted that many post-Soviet countries, in the preambles to their constitutions, have enshrined the fact of the development of their statehood over centuries and millennia. Therefore, the article substantiates the correctness of the choice made by the Republic of Kazakhstan in enshrining in the draft of the new Constitution the millennial history of the development of its statehood.The example of Azerbaijan is provided, where the preamble affirms the centuries-old traditions of statehood and historically confirms the restoration of territorial integrity, including the return of Nagorno-KarabakhKeywords: Kazakhstan, Azerbaijan, statehood, restoration, independence, Constitution, historical and legal continuity, international law, territorial integrity